Leadership Education at Pondok Modern Darussalam Gontor Putra Campus 1, Ponorogo - Nurul Salis Alamin; Syarifah; Defi Firmansyah; Riza Ashari; Neri Wijayanti (Attanwir : Jurnal Keislaman dan Pendidikan, 2024)
Leadership is the process of leading a group towards its goals. Pondok Modern Darussalam Gontor, an Islamic boarding school educational institution, emphasizes social orientation and leadership in its students. Its motto is "high-minded, able-bodied, knowledgeable, and free-thinking." In order to provide discourse, input and new ideas regarding efforts to produce cadres with character so that they can be used in Islamic boarding schools in general, this discussion aims to reveal the advantages and disadvantages of leadership education held in one of the Islamic boarding schools. boarding school. modern. Pondok Modern Darussalam Gontor intends to appoint a strong and militant leader on this basis.